Complications of external cephalic version: a retrospective analysis of 1121 patients at a tertiary hospital in Sydney. (16th June 2016) - Rodgers, R; Beik, N; Nassar, N; Brito, I; de Vries, B
Abstract : Objective: To report the complication rate associated with external cephalic version (ECV) at term. Design: Single‐centre retrospective study. Setting: A major tertiary hospital in Sydney, Australia. Population or Sample: All women who underwent an ECV at Royal Prince Alfred Hospital from 1995–2013 were included. Methods: ECV was attempted on all consenting women with a breech presentation at term in the absence of contraindications. Complications were classified as minor (transient cardiotocography abnormalities, ruptured membranes, small antepartum haemorrhage) or serious (fetal death, placental abruption, fetal distress requiring emergency caesarean section, fetal bone injury, cord prolapse). ECV success rates and rate of reversion to breech were recorded. Main outcome measures: The primary outcome was the incidence of serious complications. Secondary outcome measures were the rate of minor complications and reversion to breech. Results: Of 1121 patients that underwent ECV, five (0.45%) experienced a serious complication. There was one placental abruption, one emergency caesarean section for fetal distress and two cord prolapses. There was one fetal death attributable to a successful ECV. Forty‐eight women (4.28%) experienced a minor complication. Reversion to the breech occurred in sixteen patients (3.32%). Conclusion: ECV at term is associated with a low rate of serious complications. Tweetable abstract: Study of 1121 consecutive ECV attempts shows low rate of complications although one fetal death reported. Tweetable abstract: Study of 1121 consecutive ECV attempts shows low rate of complications although one fetal death reported.